Analysis of The Influence of Risk Management And Hospital Management Information System on The Performance of Regional Public Hospitals (Empirical Study at Regional General Hospitals in Lampung Province) - Pratama, M. Renardi Merdian; Yuliansyah, Yuliansyah; Dewi, Fajar Gustiawaty (InJEBA : International Journal of Economics, Business and Accounting, 2024)
As health service providers, hospitals have a big responsibility to provide high quality services. This is achieved by paying attention to security, health and occupational safety aspects in providing health services. One of the main efforts is through identification, assessment and risk management to minimize the possibility of unwanted risks and injuries for patients and medical personnel involved. Problem Does risk management have a significant effect on the performance of regional hospitals in Lampung Province? Does the Hospital Management Information System (SIMRS) have a significant effect on the performance of Regional Hospitals in Lampung Province. The research method used in this research is quantitative descriptive research using survey methods. The results of the research are that risk management has a positive and significant influence on the performance of Regional General Hospitals (RSUD). This is proven by the path analysis coefficient data showing that risk management contributes 35.9% to improving hospital performance. The Hospital Management Information System (SIMRS) has a positive and significant influence on the performance of Regional General Hospitals (RSUD). This research shows that SIMRS contributed 63.7% to improving RSUD performance, which is reflected in the path analysis coefficient value of 0.637. The implication of the finding that risk management has a positive and significant influence on the performance of Regional General Hospitals (RSUD) is the need to improve risk management strategies by hospital management. This may include developing and implementing comprehensive risk management policies and procedures, ongoing training for staff on risk identification and mitigation, and improving risk monitoring and evaluation systems.